A Student Mediator Legal Review of Land Acquisition for the Serang Regency Government Center: Case Study of Decision No. 174/Pdt.G/2024/PN.Srg - Siti Marina; M. Nassir Agustiawan; Dian Samudra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the legal review of the land acquisition process for the construction of the Serang Regency Government Center with a focus on the case study of Decision No. 174/Pdt.G/2024/PN.Srg. The main problem in this study is the dispute between the landowners and the local government regarding ownership status, land acquisition procedures, compensation determination, and the compliance of the stages implemented with the provisions of laws and regulations, especially Law No. 2 of 2012 concerning Land Acquisition for Development in the Public Interest. This study uses a normative juridical method with a case study approach through analysis of court decisions, laws and regulations, and administrative documents of land acquisition. The results of the study indicate that land acquisition for the project has not fully met the principles of transparency, legal certainty, and justice as mandated in the regulations. Decision No. 174/Pdt.G/2024/PN.Srg emphasizes the importance of valid proof of ownership, substantive deliberation procedures, and the government's obligation to ensure that community rights are fulfilled proportionally. In conclusion, this dispute provides important lessons regarding the need to improve land acquisition governance to be more accountable, participatory, and in accordance with legal norms in order to prevent similar conflicts in the future.